2005
DOI: 10.1002/bem.20114
|View full text |Cite
|
Sign up to set email alerts
|

Localized effects of microwave radiation on the intact eye lens in culture conditions

Abstract: A novel experimental system was used to investigate the localized effects of microwave radiation on bovine eye lenses in culture for over 2 weeks. Using this setup, we found clear evidence that this radiation has a significant impact on the eye lens. At the macroscopic level, it is demonstrated that exposure to a few mW at 1 GHz for over 36 h affects the optical function of the lens. Most importantly, self-recovery occurs if the exposure is interrupted. At the microscopic level, close examination of the lens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…For instance, World Health Organization [17] has taken the low-level energy absorption as one of the primary research topics of possible adverse health effects of electromagnetic fields. Dovrat et al [18] also believe that the energy absorbed in the tissue should be paid more attention in determining the safety standards because SAR lower than the safety standard limit may also lead to the similar effect caused be the SAR higher than the safety standard.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, World Health Organization [17] has taken the low-level energy absorption as one of the primary research topics of possible adverse health effects of electromagnetic fields. Dovrat et al [18] also believe that the energy absorbed in the tissue should be paid more attention in determining the safety standards because SAR lower than the safety standard limit may also lead to the similar effect caused be the SAR higher than the safety standard.…”
Section: Introductionmentioning
confidence: 99%
“…We will mainly focus on the eyes due to its sensitivity to electromagnetic fields [18][19][20][21][22]. This is because eyes are close to the antenna and directly exposed to the microwave without the protection of skin and fat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dovrat et al [5] reported impaired optical function of the bovine lens due to damage of lens fibers after RF exposure. RF radiation on rabbit lens showed various biochemical changes in the form of altered protein expression on cell membranes of lens epithelial cells, which declined cell proliferation, and lens epithelial cells damage and opacity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on animal models have shown that RFR exposure caused deformation of heat labile enzyme glutathione peroxidase that protects lens cell proteins and membrane lipids from oxidative damage [11]. The structural damages are in the form of granular degeneration of the lens cell epithelium at the equator, appearance of large spherical or ovoid "balloon cells, " smaller cells with condensed nuclei, and damaged cytoplasm with pyknosis [4,5,12].…”
Section: Introductionmentioning
confidence: 99%